Symposium 2: Networked learning & the challenges for Higher Education: Linking today with the future: Symposium Introduction - Burkle, Martha (Proceedings of the International Conference on Networked Learning, 2018)
The possibility of connectivity that digital technologies and the Internet have brought for students and their peers, and for faculty and their colleagues, is analysed in this paper from 3 perspectives: Impact on knowledge access, impact on instructional design, impact on teaching and learning. Papers presented in this symposium suggest that digital technologies have contributed to the radical transformation of these areas, particularly in the last decade. An emphasis is made by the authors in this panel with regard to the importance of focusing on the role that networked learning plays when defining content, design, and learner-faculty interactions inside and outside the classroom. Participants in the symposium will be invited to reflect on the research and policy analysis presented by the authors in the symposium and will be then invited to participate in the discussion by sharing their experiences on the topic. Paths for further examination will be discussed and a panorama for future exploration will be determined.